The Determinant Line Bundle for Fredholm Operators: Construction, Properties, and Classification - Zinger, Aleksey (MATHEMATICA SCANDINAVICA, 2016)
We provide a thorough construction of a system of compatible determinant line bundles over spaces of Fredholm operators, fully verify that this system satisfies a number of important properties, and include explicit formulas for all relevant isomorphisms between these line bundles. We also completely describe all possible systems of compatible determinant line bundles and compare the conventions and approaches used elsewhere in the literature.